MODEL SIMULASI BANJIR MENGGUNAKAN DATA PENGINDERAAN JAUH, STUDI KASUS KABUPATEN SAMPANG DENGAN MENGGUNAKAN METODE GRIDDED SURFACE SUBSURFACE HYDROLOGIC ANALYSIS - Haryani, Nanik Suryo; Pasaribu, Junita Monika; Ambarwati, Dini Oktavia (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2012)
The problem of flood that yearly occurred in Sampang district was due to the very large amount of runoff flow to the Sampang Cit, very high sedimentation in the river that crosses the city, as well as the lack of good drainage system especially in urban residential areas. Some of that problems eventually can lead to flooding in the City of Sampang. The method used for flood simulation model was GSSHA (Gridded Surface Subsurface Hydrologic Analysis), which is able to produce a good hydrological components. The data used data in this research among others are: Qmorph, DEM-SRTM (Digital Elevation Model-Shuttle Radar Topography Mission), SPOT-5 of 2010, land map, river cross sections and field data. This flood simulation model research resulting flood discharge, which is described in the hydrograph and flood depth calculations. The peak discharge resulted in several catchment areas (CA): Klampis CA is 5.40 m³/s, Jelgung CA is 364788.9 m³/s, Kamoning CA is 32.40 M³/s, and 3 CAs which are associated with the above CAs is 174059 m³/s.